2023
DOI: 10.3390/plants12071572
|View full text |Cite
|
Sign up to set email alerts
|

Rosa davurica Inhibited Allergic Mediators by Regulating Calcium and Histamine Signaling Pathways

Abstract: Rosa davurica Pall. exhibits antioxidant, antiviral, and anti-inflammatory properties; however, its pharmacological mechanism in allergy is yet to be understood. This study confirmed the effects of R. davurica Pall. leaf extract (RLE) on allergy as a new promising material. To evaluate the therapeutic potential of RLE against allergy, we investigated the effects of RLE on the regulatory β-hexosaminidase, histamine, histidine decarboxylase (HDC), Ca2+ influx, nitric oxide (NO), and cytokines induced by lipopoly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Following the harvest, a total of 4 samples, each representing three replicates per experimental plot, were collected for analysis. The method of Oh S et al was used to extract R. davurica exactly as it was [10].…”
Section: Sample Preparationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Following the harvest, a total of 4 samples, each representing three replicates per experimental plot, were collected for analysis. The method of Oh S et al was used to extract R. davurica exactly as it was [10].…”
Section: Sample Preparationsmentioning
confidence: 99%
“…A recent study revealed that a 30% ethanol extract from R. davurica inhibited UVB-induced photoaging [9]. Also, a similar extract inhibited the release of cytokines and histamine in activated DNP-IgE mast cells, thereby exhibiting potential in managing allergic diseases [10].…”
Section: Introductionmentioning
confidence: 99%
“…R. davurica fruit (RDP-F) is generally used as a traditional medicine in many countries such as China, Korea, and Japan [ 15 , 16 , 17 ]; however, only in China is it widely used in food. The health-promoting effects of R. davurica , such as its antioxidant, anti-inflammatory, antiviral, and hypoglycemic activities, are well-established [ 17 , 18 , 19 , 20 ]. R. davurica fruit (RDP-F) is also commonly consumed as a beverage and health food in China [ 21 ].…”
Section: Introductionmentioning
confidence: 99%